Two-dimensional domain structures in Lithium Niobate via domain inversion with ultrafast light - Chen, X.; Karpinski, P.; Shvedov, V.; Wang, B.; Trull, J.; Cojocaru, C.; Boes, A.; Mitchell, A.; Krolikowski, Wieslaw; Sheng, Y. (Photonics Letters of Poland, 2016)
Periodic inversion of ferroelectric domains is realized in a lithium niobate crystal by focused femtosecond near-infrared laser beam. One and two-dimensional domain patterns are fabricated. Quasi-phase matched frequency doubling of 815nm light is demonstrated in a channel waveguide with inscribed periodic domain pattern with conversion efficiency as high as 17.45%. Full Text: PDF References J. A. Armstrong, N. Bloembergen, J. Ducuing, and P. S. Pershan, "Interactions between light waves in a nonlinear dielectric," Phys. Rev. 127, 1918 (1962). CrossRef M. Houe and P.D. Townsend, "An introduction to methods of periodic poling for second-harmonic generation," J. Phys. D 28, 1747 (1995). CrossRef Y. Sheng, T. Wang, B. Ma, E Qu, B. Cheng, and D. Zhang, "Anisotropy of domain broadening in periodically poled lithium niobate crystals," Appl. Phys. Lett. 88, 041121 (2006). CrossRef C. Y. J. Ying, A. C. Muir, C. E. Vakduvuam G. H. Steigerwald, C. L. Sones, R. W. Eason, E. Soergel, and S. Mailis, "Light-mediated ferroelectric domain engineering and micro-structuring of lithium niobate crystals," Laser Photonics Rev. 6, 526 (2012). CrossRef X. Chen, P. Karpinski, V. Shvedov, K. Koynov, B. Wang, J. Trull, C. Cojocaru, W. Krolikowski, and Y. Sheng, "Ferroelectric domain engineering by focused infrared femtosecond pulses," Appl. Phys. Lett. 107, 141102 (2015). CrossRef Y. Sheng, A. Best, H. Butt, W. Krolikowski, A. Arie, and K. Koynov, "Three-dimensional ferroelectric domain visualization by Čerenkov-type second harmonic generation," Opt. Express 16, 16539 (2010). CrossRef X. Chen, P. Karpinski, V. Shvedov, A. Boes, A. Mitchell, W. Krolikowski, Y. Sheng, "Quasi-phase matching via femtosecond laser induced domain inversion n lithium niobate waveguides," Opt. Lett. 41, 2410 (2016). CrossRef